The time game: cracking the code of TMT age versus tenure in driving organizational performance - Son-Tung Nguyen; Hsin-Mei Lin; Thuy-Dzung T. Pham (Cogent Business & Management, 2024)
This study investigates how age, tenure, and network of the top management team (TMT) affect organizational performance, using public data of listed IT companies from the USA. The Theory of Organizational Socialization (TOS) and Upper Echelon Theory (UET) lay the foundation for the research and a quantitative analysis approach is used. The findings show that TMT age has a positive interplay with organizational performance, suggesting the importance of wisdom and decision-making prowess accumulated through experience. Conversely, TMT tenure shows a negative impact on organizational performance, advocating a possible lack of flexibility or reluctance to adapt could lead to unfruitful business outcomes. Moreover, the TMT network, by promoting effective communication, collaboration, and knowledge-sharing, creates a strong social environment among the members and ultimately enhances the organization's performance.
Keywords: 650; Age; tenure; network; organizational performance; top management team